Nucleotide sequence of metF, the E. coli structural gene for 5-10 methylene tetrahydrofolate reductase and of its control region. - Saint-Girons, I (1983)
The nucleotide sequence of the E.coli metF gene (888 nucleotides), coding for 5-10 methylene tetrahydrofolate reductase, has been determined. The metF gene product was identified in maxicells and found to be a protein of subunit molecular weight 33,000, in agreement with the size of the coding region. The starting point for metF transcription was determined by S1 nuclease mapping. No structural evidence was found for an attenuation mechanism regulating the independent metF transcriptional unit. Comparison of the regulatory region preceding the metF structural gene with the 5' flanking region of the metBL operon shows some homology spanning 24 nucleotides. These homologous sequences could be operator structures belonging to the two transcriptional units, metF and metBL, and recognized by the same regulatory protein.